Assessing the Renaissance of Individuals in International Relations Theory. Issue 2 (25th April 2021) - Holmes, Marcus; Jordan, Richard; Parajon, Eric
ABSTRACT: The study of microfoundations, especially individuals, is enjoying a renaissance in international relations (IR) scholarship. Yet, this rise is more difficult to find in publication data. Using the Teaching, Research, and International Policy (TRIP) journal-article database, we show that only 13.7% of IR articles in 12 leading journals use the first image. This proportion remains approximately the same from 1980 through 2018. Interrogating the data, we show that this distribution does not stem from epistemological or methodological commitments, such as positivism, quantitative analysis, or formal modeling. We suggest several reasons for this apparent disjuncture between qualitative assessments of the rebirth of first-image theorizing and the quantitative data that imply a slower or perhaps more limited return.